Social Trust and Economic Development: Spatial Econometric Analysis - Ozcan, Burcu; Zeren, Fatma (Eskisehir Osmangazi Univ, Fac Education, 2013)
Social capital highlights intangible elements in a society, such as trust, reciprocity norm and social networks. It is now handled and discussed by many scholars in different disciplines. Economists have started to analyze social capital in applied and theoretical studies since 1990s. While some of these scholars accept it as a new capital type, others do not. Thus, it can be said that it has a disputable place in economics discipline. However, economists especially examine its impact on countries' economic development levels and generally accept its importance and contributions to development. In this study, we examine the relationship between economic development and social trust by using spatial econometrics method in a sample of 27 European countries over a time span from 1999 to 2009. The findings suggest that a country's social trust level has positive impacts on economic development.
Keywords: Social Capital; Social Trust; Economic Development; Spatial Econometrics